Determining the diversity and relative abundance of coral taxa in wild spawning slicks for effective restoration - Marquardt, Bailey; Elder, Holland; Yeoh, Yun Kit; Heyward, Andrew; Randall, Carly J.; Harrison, Peter L.; Logan, Murray; Howells, Emily (Frontiers in Ecology and Evolution, 2025)
Coral reefs are increasingly threatened by climate change-induced stressors, including marine heatwaves, which can lead to coral mortality, reduced reproductive output, and compromised natural recovery. Successful coral reef recovery requires the settlement of coral larvae and recruitment in degraded areas, replenishing coral communities and promoting resilience. Some restoration strategies involve utilizing natural spawning slicks, composed of coral gametes and embryos, to produce larvae to reseed reefs. However, verifying the taxonomic composition of these slicks is challenging. Here, we tested the performance of two coral ITS primer sets, CoralITS2 and CoralITS2_acro, on mock communities to evaluate their ability to capture genera composition and relative abundances. Both primer sets demonstrated high accuracy (>97%) in detecting and quantifying coral taxa. Subsequently, these primers were applied to wild-collected spawning slicks from the Great Barrier Reef, revealing variation in scleractinian (reef-building) coral community composition among slicks. For the CoralITS2_acro assay, Acropora was consistently the most abundant resolved genus detected across wild slick sample sites, with the exception of samples from the Whitsundays region, where Platygyra was dominant. The CoralITS2 assay successfully differentiated reef-building (Scleractinian) corals from other co-occurring spawning taxa, such as soft corals, anemones, and sponges, and revealed that these other co-spawners dominated slicks at two sites. Our findings underscore the potential of eDNA-based monitoring as a scalable tool to confirm the presence and relative abundance of diverse coral assemblages in natural slicks, informing restoration efforts. By enabling the characterization and comparison of slick composition across large spatial and temporal scales, eDNA metabarcoding can support restoration practices that align with the ecological requirements of reef ecosystems, safeguarding biodiversity and promoting resilience against future disturbances.